Dissemination of Pseudomonas syringae pv. actinidiae through pollen and its epiphytic life on leaves and fruits - STEFANI, EMILIO; GIOVANARDI, DAVIDE (Phytopathologia Mediterranea, 2012)
The role of pollen in disseminating Pseudomonas syringae pv. actinidiae (Psa ) in kiwifruit orchards was investigated and the survival of the pathogen as an epiphyte on leaves and fruits was followed, from pollination time until the pre-harvest season. Pollen with natural inoculum was obtained from an infected orchard and pollen harvested without any contamination by Psa was experimentally inoculated at approximately the same contamination level. Two pollination techniques were used in glasshouse experiments: dusting and spraying. In parallel, field trials in commercial orchards were carried out: two plots were designed in two orchards, where bacterial canker was present at low incidence. From petal fall to 3 weeks before harvesting, leaf and fruit samples were taken and analysed for the presence of Psa, using two different PCR protocols and direct isolation. Results confirmed the dissemination of Psa through pollen, especially when using the aqueous suspensions. Both in glasshouse experiments and in the orchards Psa was found as an epiphyte for several weeks after pollination. Pathogen populations on leaves were, initially, 10 to 100 times less than on fruitlets. As the summer continued, the epiphytic contamination levels of fruits decreased constantly, being no more detectable from early August, whereas Psa was present at detectable levels on leaves until early October, approx. 20 days before harvesting time. Our results confirmed the role of pollen in disseminating Psa, the long epiphytic survival of the pathogen on kiwifruit leaves and the increasing unsuitability of fruits to harbour detectable, epiphytic populations of the bacterium through the summer season in commercial orchards with low disease incidence, when they are reaching the final development stage. Thus, kiwifruit surfaces do not appear to be a suitable niche for a long term survival of Psa as an epiphyte and, therefore, kiwifruits should not represent a pathway for Psa dissemination and pose a negligible risk for the introduction of the pathogen into new areas.